INVESTIGATING THE IMPACT OF MICROTEACHING LESSON STUDY TO THE PROSPECTIVE ENGLISH TEACHERS’ SELF-EFFICACY - Sumarno, Wahyu Kyestiati (STKIP Muhammadiyah Pringsewu, 2019)
This study aims to investigate the English pre-service teachers’ self-efficacy after experiencing a three-week microteaching lesson study project. There were thirty-nine pre-service teachers participated in this study. In a group of five persons, they were assigned to do three times of thirty-minutes-microteaching practices. Microteaching lesson study model was used in this research. A questionnaire and an interview were distributed after the project was completed. The questionnaire measured the students’ self-efficacy while the interview explored the student-teachers’ perceptions toward the project. Results indicated that the microteaching lesson study has a good impact on the self-efficacy of the prospective English teachers.